Biomechanical Evaluation of Recurrent Dissociation of Modular Humeral Prostheses - Daniel B. Luckenbill; Mike F. Iossi; Alyssa M. George Whitney; Danielle Miller; Lynn A. Crosby; Tarun Goswami (Bioengineering, 2022)
The purpose of the study was to evaluate the force and torque required to dissociate a humeral head from the unimplanted modular total shoulder replacement system from different manufacturers and to determine if load and torque to dissociation are reduced in the presence of bodily fluids. Impingement, taper contamination, lack of compressive forces, and interference of taper fixation by the proximal humerus have all been reported as possible causes for dissociation. Experimental values determined in this research were compared with literature estimates of dissociation force of the humeral head under various conditions to gain more understanding of the causes of recurrent dissociations of the humeral head. This study examined biomechanical properties under dry and wet conditions under clinically practiced methods. Mean load to dissociation (1513 N ± 508 N) was found to be greater than that exerted by the activities of daily living (578 N) for all implants studied. The mean torque to dissociation was (49.77 N·m ± 19.07 N·m). Analysis of R2 correlation coefficients and p-values (α = 0.05) did not show any significant correlation between dry/bovine, dry/wet, or wet/bovine for load, displacement, or torsional stiffness in the majority of tests performed. Wetting the taper with water or bovine serum did not reduce the dissociation force to a statistically significant degree. Torque and lack of compressive forces at the rotator cuff may be the cause of dissociation at values less than those of activities of daily living. Torque data are provided by this study, but further research is needed to fully appreciate the role of torque in recurrent dissociations.